Molecular Genetic Mapping of Two Complementary Genes Underpinning Fruit Bitterness in the Bottle Gourd (Lagenaria siceraria [Mol.] Standl.) - Wu, Xiaohua; Wu, Xinyi; Wang, Ying; Wang, Baogen; Lu, Zhongfu; Xu, Pei; Li, Guojing (Frontiers in Plant Science, 2019)
Fruit bitterness is a serious problem threatening the bottle gourd (Lagenaria siceraria [Mol.] Standl.) industry worldwide. Previous genetic studies indicated that fruit bitterness in the bottle gourd was controlled by a pair of complementary genes. In this study, based on two non-bitter landraces “Hangzhou Gourd” and “Puxian Gourd,” each of which carries a single bitterness gene, and their derived segregation populations, we mapped the complementary genes causing fruit bitterness. Quantitative trait locus (QTL) scanning based on an F2 population detected two QTLs, which was QBt.1 locating in a 17.62-cM interval on linkage group (LG)2 corresponding to a 1.6-Mb region on chromosome 6, and QBt.2 mapped to a 8.44-cM interval on LG9 corresponding to a 1.9-Mb region on chromosome 7. An advanced bulked segregant analysis (A-BSA) well validated the QTL mapping results. Sequence-based comparative analysis showed no syntenic relationship between QBt.1/QBt.2 and the known bitterness genes in cucumber, melon, and watermelon, suggesting that causal genes underlying QBt.1 and QBt.2 were not direct orthologs of the reported cucurbit bitterness genes. Our results shed light on the molecular genetic mechanisms underlying fruit bitterness in the bottle gourd and is useful to guide breeders to properly select parental lines to avoid the occurrence of bitter fruits in breeding programs.